Increasingly distant from life: problem setting in the organization of home care - Ceci, Christine (Nursing philosophy, 2008)
The analysis undertaken in this paper explores the significance of a central finding from a recent field study of home care case management practice: a notable feature of case management work is the preparation of an orderly, ordered space where care may be offered. However, out of their encounters with an almost endless variety of situations, out of people's diverse narratives of need, case managers seem able to pick out only limited range of recognized needs to which to respond and demonstrate a series of responses themselves equally limited. Though this observation suggests a kind of efficiency that is currently highly valued within healthcare systems, it also underlines the system's inability to engage difference and variability in a meaningful way. This inability or limitation in effectively engaging difference is conceptualized here as, in some sense, a problem, and the nature of this problem is explored through the rhetorical process of problem setting. The central question becomes how might we develop and deploy an orderly and coherent system of care without essentializing people's experiences, without treating these experiences reductively, without, in a Foucaultian frame of reference, allowing what can be understood as similarity or resemblance among clients and situations to be folded back into sameness? As we encounter complexity, variability and difference in practice, how should we treat it?